Menyingkap Hubungan Kompleks: Peran Strategis Lingkungan dan Sosial Terhadap Nilai Perusahaan : Bahasa Indonesia - Rahman, Firdaus Abdul; Saputra, Dian; Yovan Allif Ananda (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2024)
This study examines the relationship between Green Accounting, Carbon Emissions, Eco-efficiency, Gender Diversity, and firm value in the raw materials sector. Using a sample of 50 companies listed on the Indonesia Stock Exchange, data was collected from financial statements, annual reports, and sustainability reports. Analyses conducted using SMARTPLS 3 showed a significant relationship between Carbon Emissions, Environmental Efficiency, Gender Diversity, and firm value. However, the cross-sectional design of this study limits its ability to observe long-term trends. Future longitudinal studies may provide a more in-depth understanding of these dynamics. The findings highlight how companies in the raw materials sector can increase firm value by adopting sustainable practices, such as reducing Carbon Emissions, improving environmental efficiency, and promoting Gender Diversity.